Perceptions of Factors Affecting Milk Quality and Safety among Large- and Small-Scale Dairy Farmers in Zimbabwe - Annah Shingirai Paraffin; Titus Jairus Zindove; Michael Chimonyo (Journal of Food Quality)
The study investigated the perceptions of milk producers on milk quality and safety. Randomly selected large-scale farmers (n=158) and small-scale farmers (n=186) were surveyed using semistructured questionnaires. An ordinal logistic regression was used to estimate the probability of farmers considering milk quality and safety important. Large-scale farmers were 3 times more likely to consider that breed affects milk quality compared to their small-scale counterparts. Farmers aged over 30 years were 3 times more likely to indicate that hygiene affected milk quality. The likelihood of milk transportation affecting its quality was 4 times higher in small-scale farmers compared to large-scale producers. Postmilking contamination of milk was perceived to occur during transportation by small-scale farmers, whilst commercial farmers ranked storage as the important source of contamination after milking. Udder diseases were ranked first by large-scale farmers while small-scale farmers ranked milking environment as the major cause of milk spoilage. The likelihood of milk safety being important was two times higher in large farms compared to small-scale farms. Intervention programmes on milk safety should mainly target small-scale dairy farmers since they are less concerned about milk quality and safety.